Dendritic cells control tertiary lymphoid structure development and maintenance in cancer - Raphaël Mattiuz; Jesse Boumelha; Emmanouil Aerakis; Jessica Le Berichel; Pauline Hamon; Laszlo Halasz; Abishek Vaidya; Brian Y. Soong; Emir Radkevich; Hye Mi Kim; Matthew D. Park; Romain Donne; et al. (Science, 2026)
Tertiary lymphoid structures (TLSs) are associated with immunotherapy response, yet the mechanisms controlling their formation and maintenance remain unclear. Using spatial transcriptomics and multiplex imaging across human tumors, we found that CCR7 + mature dendritic cells (DCs) accumulate in TLSs. In a mouse non–small cell lung cancer model that forms mature TLSs, we show that early TLS development requires interferon-γ (IFN-γ)–driven type 1 conventional dendritic cell (cDC1) maturation, migration to tumor-draining lymph nodes (tdLNs), and T cell recruitment. As tumors progress, TLSs persist independently of tdLN T cell egress, coinciding with cDC1 accumulation within intratumoral CCL19 stromal hubs. There, cDC1–major histocompatibility complex class 1 (MHC-I) and –MHC-II concomitant antigen presentation, along with CD40 signaling, sustain TLS, T follicular helper (T FH ) cell pool, germinal centers, and tumor-specific immunoglobulin G (IgG). These findings highlight local mature cDC1s as key TLS orchestrators and potential targets to enhance antitumor TLS function.